2015
DOI: 10.24191/jeeir.v3i1.9049
|View full text |Cite
|
Sign up to set email alerts
|

Can Values of Honesty, Hard Work, Loyalty and Discipline Predict Entrepreneurial Orientation of Muslim Owner Managers?

Abstract: The purpose of the present study is twofold: first, to investigate the true values of Muslim owner managers; second, to examine the impact of these values on entrepreneurial orientations of Muslim small-scale entrepreneurs. 850 Muslim owner managers were selected randomly using the sampling frame provided by MajlisAmanah Rakyat Malaysia (MARA). 162 completed questionnaires were collected and analyzed. For this paper only two dimensions of entrepreneurial orientations were analyzed: proactive orientation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(15 reference statements)
0
9
0
Order By: Relevance
“… Work hard: out of 30 teachers stated that the principal always worked hard, by always participating in productive activities carried out by the teachers, for example memorizing the Koran, coaching and mentoring to take part in the competition, giving examples of product-based learning, and working hard to innovate to make learning Media. Mohd et al (2015) that the attitude of working hard is positively related to the orientation of innovation in entrepreneurial learning..…”
Section: Effect Of Principal's Entrepreneurship Behavior On Teacher'smentioning
confidence: 92%
“… Work hard: out of 30 teachers stated that the principal always worked hard, by always participating in productive activities carried out by the teachers, for example memorizing the Koran, coaching and mentoring to take part in the competition, giving examples of product-based learning, and working hard to innovate to make learning Media. Mohd et al (2015) that the attitude of working hard is positively related to the orientation of innovation in entrepreneurial learning..…”
Section: Effect Of Principal's Entrepreneurship Behavior On Teacher'smentioning
confidence: 92%
“…This is in accordance with the Hadith that mentioned about honesty (one of the many Islamic values) as one of the best business strategy. Past researches (Schwartz, 2009;Mohd, Kamaruddin, Yahya, & Sanidas, 2015;Mohd, Kamaruddin, Muda, Hassan, 2016) have verified that benevolent values are important determinants of performance. However, the values studied were not specifically related to Islamic faith.…”
Section: Organizational Performancementioning
confidence: 99%
“…All these were not related to religious values. Quite recently, Mohd et al, (2015) studied the religious values of Muslim entrepreneurs but investigating its impact on entrepreneurial orientations, instead of performance. They suggested that religious values had significant impact on the entrepreneurial orientation of firm owners.…”
Section: The Empirical Evidence Of the Relationships Between Values And Performancementioning
confidence: 99%
“…In addition to hard work, the discipline has a positive relationship with innovation. It was also explained that innovation requires a strategic plan that is systematic and hard work, and individuals who value discipline and hard work believe that by being innovative, a person can succeed in business/entrepreneurship [18].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%